Philosophy of Early Childhood Education Management in Indonesia - Shofaryanty Nurhayati Saepudin; A Denih; Ajeng Puspitasari Santosa (al-Afkar, Journal For Islamic Studies, 2024)
Implementation management is related to the administration and management of institutions, relating to the administration, regulation or structuring of activities in institutions. Management comes from the word to manage which means to manage, lead or direct. Management plays a very important role in a PAUD because the success of a PAUD cannot be separated from good management. The type of research used is literature study. Literature study is a required activity in research, especially   academic research whose main aim is to develop theoretical aspects as well as aspects of practical benefit. Literature studies are carried out by each researcher with the main aim of finding a basis for obtaining and building a theoretical basis, framework of thinking, and determining temporary assumptions or also known as research hypotheses. So that researchers can group, allocate, organize and use a variety of libraries in their field. The results of this research show that the philosophy of early childhood education aims to help formulate the role of the process of providing education for early childhood in society, interpret the role of education, and direct that role to realize the goals of serving society both now and in the future. will come. The philosophy of early childhood education is needed to reveal and examine the realities that are occurring in the midst of the early childhood education process.